Understanding Needs for Chronic Musculoskeletal Pain Management in a Northern Dene and Métis Community: A Community Based Needs Assessment - Tayah Zhang; Brenna Bath; Veronica McKinney; Jaris Swidrovich; Rachel Johnson; Heather Foulds; Nadia Makar; Melanie Montgrand; Stacey Lovo (Canadian Journal of Pain)
Background Chronic musculoskeletal (MSK) pain disproportionately affects Indigenous Peoples, and rural/remote communities face significant barriers in accessing care. La Loche, a Dene/Métis community in northern Saskatchewan, has limited access to specialized chronic pain management services and specialized health providers.Aims The aim of this needs assessment was to gain insight into the community’s priorities, strengths, and concerns regarding chronic MSK pain management. Community engagement and relationship building were essential to ensure that cultural protocols were respected and community worldviews were accurately represented.Methods A community-directed needs assessment was conducted in collaboration with local health care providers and community members. To ensure appropriate representation of community-led priorities, reflexive thematic analysis was utilized and rooted within interpretive description and informed by community-based participatory research and Two-Eyed Seeing. Open discussions were conducted in person, over the phone, or via Zoom in a semistructured format. Thirteen individuals were interviewed (eight community members, five health care professionals).Results Interviews conducted with community members and health care providers were analyzed separately. Both yielded the same four major overarching themes: (1) impact of pain on daily living, (2) barriers limiting access to care and the understanding of pain between health care provider and patient, (3) systemic oppression and negative experiences with health care, and (4) strength-based solutions.Conclusions Five recommendations were developed to promote culturally safe and patient-centered environments for chronic MSK pain communication and future care delivery: (1) person-centered and community-directed care, (2) clinic model and staffing requirements, (3) practitioner education and awareness, (4) community education and awareness, and (5) community resources.